Effect of variations in blade width on vertical shaft kinetic water turbine power - Yani, Ahmad; Ratnawati, Ratnawati; Anoi, Yano Hurung; Patabang, Yonatan; Risaldi, Risaldi; Zulkifli, Zulkifli (International Journal of Multidisciplinary Approach Research and Science, 2023)
Various studies and observations have been carried out to produce a turbine design that suits the needs and the relatively low flow speed is a challenge that currently still requires further research. ThereforeThe aim of this research is to determine the effect of variations in the width of the bowl blade on the vertical shaft kinetic water turbine power.The research method used is an experimental method with an experimental design on a laboratory scale. Tests were carried out on three variations of blade width, from the results of the study it can be concluded that increasing the water flow rate, turbine rotation, and the ratio of tangential speed to the turbine blade width can increase the kinetic water turbine power. In this study, variations in blade width were 10 cm, 11 cm, and 12 cm. Increasing turbine blade sheets increased turbine power due to the additional mass of the flow hitting the turbine blades thereby affecting the kinetic water turbine power. Analysis of the water flow rate shows that the maximum turbine power occurs at a blade width of 12 cm and a discharge of 0.017 m3/second with a turbine power value of 25.455 Watt. Analysis of turbine rotation, Maximum turbine power occurs at a blade width of 12 cm and rotation of 80 rpm with a turbine power value of 23,864 Watts. Meanwhile, analysis of the tangential speed ratio shows that the maximum turbine power occurs at a blade width of 12 cm and at a tangential speed ratio of 0.5 rad/s2 with a turbine power value of 23,864 Watts. Keywords: Blade width, power, kinetic turbine, vertical shaft.